2016
DOI: 10.1213/xaa.0000000000000343
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Operating Room Management Educational Tool

Abstract: In 2010, our department instituted a nonclinical, administrative rotation in operating room management for anesthesiology residents. Subsequently, we mandated the rotation for all senior anesthesiology residents in 2013. In 2014, under the auspices of the American Society of Anesthesiologists, we developed a web-based module covering the basics of finance, accounting, and operating room management. A multiple-choice test was given to residents at the beginning and end of the rotation, and we compared the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…While the importance of acquiring nontechnical skills and knowledge during residency is recognized across multiple specialties and by the ACGME, residency programs are still exploring ways to enable residents to improve in these areas. 25,26 Our study demonstrated that a multimodal, 1-month educational intervention in practice management improved practice management knowledge acquisition of senior anesthesiology residents by 18.8%. Further, qualitative analysis revealed that the study intervention was perceived as valuable and educational to participants.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…While the importance of acquiring nontechnical skills and knowledge during residency is recognized across multiple specialties and by the ACGME, residency programs are still exploring ways to enable residents to improve in these areas. 25,26 Our study demonstrated that a multimodal, 1-month educational intervention in practice management improved practice management knowledge acquisition of senior anesthesiology residents by 18.8%. Further, qualitative analysis revealed that the study intervention was perceived as valuable and educational to participants.…”
Section: Discussionmentioning
confidence: 69%
“…Right Time, Right Cost. " 6 This 1-hour online module covers the basics of OR management financing and accounting. Residents were provided a password and instructed to access the module after completing the reading assignments.…”
Section: Web-based Modulementioning
confidence: 99%
See 2 more Smart Citations
“…Patient information and surgical consumables can be connected to the hospital's Internet platform for information exchange and communication, through radio frequency identification (RFID), two-dimensional codes, infrared sensors, laser scanners, mobile personal digital assistants and other information sensing devices (22,23). The big data-based surgical management method can realize the intelligent identification, positioning, tracking, monitoring and management of single surgical equipment (24). The multimodal surgical information identification system integrates and interconnects the multi-source data and information island systems of various departments in the hospital, and builds the quality and safety information management system of the hospital operation department together with the management process of the operation department (25).…”
Section: Discussionmentioning
confidence: 99%